The extent to which Arabic language teachers possess the necessary educational competencies to teach literary texts at the secondary level, and the extent of their practice in Zarqa Governorate - Al-Zawahrh, Khadeejeh Nawafa (Journal of Educational and Psychological Sciences, 2022)
This study aimed at the extent to which Arabic language teachers possess the educational competencies necessary to teach literary texts at the secondary level and the extent to which they are practiced in Zarqa Governorate. , who are studying Arabic for the secondary stage, and the necessary data were collected using a questionnaire, and it was applied to the study sample. The results of the study revealed that the study sample’s evaluation of the extent to which the study sample possesses the educational competencies necessary for teaching literary texts at the secondary level and the extent to which they are practiced in Zarqa Governorate, from their point of view, was average. Obtaining advanced training courses in educational competencies necessary for teaching literary texts in educational situations in the Ministry of Education.
Keywords: educational competencies; literary texts; Arabic language teacher; high school